Long-Term Outcome of Step-Cut Ulnar Shortening Osteotomy for Ulnar Impaction Syndrome. (2nd November 2016) - Papatheodorou, Loukia K.; Baratz, Mark E.; Bougioukli, Sofia; Ruby, Tyler; Weiser, Robert W.; Sotereanos, Dean G.
Abstract : Background: Extra-articular ulnar shortening osteotomy is a common procedure for the surgical treatment of ulnar impaction syndrome. Several techniques for this osteotomy have been developed to avoid the morbidity associated with a standard transverse osteotomy. However, these techniques require special instrumentation and are expensive. The purpose of this study was to evaluate the outcome of step-cut ulnar shortening osteotomy without special jigs for ulnar impaction syndrome. Methods: A retrospective study of 164 consecutive patients who underwent step-cut ulnar shortening osteotomy between 2000 and 2010 was performed. The long arm of the step-cut osteotomy was oriented in the coronal plane parallel to the long axis of the ulna. The short arms of the osteotomy were perpendicular to the long axis in the axial plane. Fixation was performed with a palmar 3.5-mm standard neutralization plate and a lag screw. The goal of the osteotomy was to reduce ulnar variance, which was assessed in all patients with pronated grip-view radiographs preoperatively and postoperatively. Preoperative ulnar variance ranged from +1 to +6 mm. Results: All patients were followed for at least 24 months. Union of the osteotomy site was achieved at a mean of 8.2 weeks. The union rate was 98.8%. There were 2 cases of nonunion, which required additional surgery. The mean postoperative ulnar variance was +0.2 mm (range, −1 to +1.5 mm) after a mean overall ulnar shortening of 2.5 mm. All patients returned to their previous work, in a mean of 4 months. The plate was removed from 12 patients because of plate-related symptoms. No other complications were encountered. Conclusions: The step-cut ulnar shortening osteotomy provides ample bone-to-bone contact and simplifies control of rotation. Stable internal fixation with standard techniques allowed an early return to functional activities. Palmar placement of the plate diminishes the need for plate removal. This is a simple and less expensive technique for ulnar shortening that does not require the use of special instrumentation in patients with ulnar impaction syndrome. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.